Persian Population of Terek Region in Second Half of 19th — Early 20th Centuries - Z. V. Kanukova (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The migration movement of the population of Northern Iran to the Terek region in the era of its post-reform modernization in the second half of the 19th — early 20th centuries is considered. The reasons, nature, time and features of the migration history of the Iranians are considered. The novelty of the study lies in the identification of specific starting points of migration on the territory of Iran, routes of advancement on Russian territory and places of settlement in the Terek region. Particular attention is paid to the study of the social composition and economic adaptation of migrants. On the basis of archival sources, corrections were made to the prevailing ideas about social strata, about the labor nature of migration, and about the ethnic composition of migrants. Significant differences in the situation of migrants in the Transcaucasia and the North Caucasus are revealed. The dependence of these differences on the characteristics of the host society — the Terek region during the period of post-reform modernization of the economy and social development -is determined. The specifics of the arrangement of Iranian migrants in national regions of the region have been determined. It is concluded that ethnic entrepreneurship was the basis of the adaptation process and the life of migrants who made a significant contribution to the development of the region’s economy.